The relationship between dietary inflammatory index and metabolic syndrome and its components: a case study in Kashi urban, Xinjiang - Zhang, Yangyi; Liu, Xiangtao; Su, Yinxia; Jiang, Yan; Cai, Junxiu; Yang, Xiaoping; Zou, Yuan; Chen, Jing; Zhao, Xingyang; Xiao, Hui (Frontiers in Nutrition, 2024)
This paper examines the association between the dietary inflammatory index (DII) and the risk of metabolic syndrome (MS) and its components among Uygur adults in Kashi, Xinjiang. We used the multi-stage random cluster sampling method to investigate the adult residents of Uighu aged over 18 years old in one county and one township/street of three cities in Kashi between May and June 2021. All dietary data collected were analyzed for energy and nutrient intake with a nutritional analysis software, followed by a calculation of DII. Logistic regression was used to estimate the association between DII and the risks of MS and its components. When the DII was taken as a continuous variable, it was significantly correlated with MS (OR=0.57, 95% CI: 0.395-0.870); there was a significant correlation between high and low density lipoproteinemia and DII (OR=1.55, 95% CI: 1.040-2.323) adjusted to sex, age, and occupation. Combined with the analysis of dietary patterns of the sample population, the DII further refined the correlation between food and components of MS. The results showed that the fruit-milk dietary pattern was negatively correlated with the prevalence of MS and hypertension, whereas the meat-and-eggs type was positively correlated with high fasting glucose and obesity. In addition, nuts, dried fruits, oil, and salt with high factor load values entered the dietary pattern matrix, laying the foundation for further research.